Strategi Komunikasi Pariwisata Dalam Meningkatkan Minat Pengunjung Destinasi Wisata Alam Gomara Swiss Kabupaten Labuhanbatu Utara - Nia Lestari (Universitas Muhammadiyah Sumatera Utara, 2023)
This research examines how the process of Tourism Communication Strategy In Increasing Visitor Interest In Gomara Swiss Natural Tourism Destinations In North Labuhan Batu Regency. This Research was conducted to find out how the Tourism Communication Strategy in Increasing Visitor Interest in the Swiss Gomara Natural Tourism Destination of North Labuhan Batu Regency. This techniques used are interview, observation and documentation techniques. The theory used in this research is Aidda Theory. The sources in this study amounted to 6 (six) people who were Tourism Managers as a unit of Village-Owned Enterprises (Bumdes Serumpun Simonis), Head of Simonis Village Chairperson of the Village-Owned Enterprises unit (Bumdes Serumpun Simonis) and 4 (four) visitors to Gomara Swiss natural tourism. The result of this study indicate that the tourism communication strategy in increasing visitor interest in Gomara Swiss natural tourist destinations has been carried out well, the need or expansion of cooperation between the management, te Tourism Office, private investors and the community so that the strategies that have been set can run according to careful planning and management to improve the quality of security, comfort and service in order to increase visitor interest